RANCANGAN BUKU PANDUAN DAN VIDEO PRAKTIKUM MATERI UJI BAHAN MAKANAN BAGI CALON GURU BIOLOGI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The competencies that must be mastered by biology subject teachersconsist of material knowledge and knowledge in carrying out biological experiments inthe right and correct way. This research is a development research that aims to see howthe quality of the design of manuals and practical videos of food material testing forprospective biology teachers. This manual and practical video were developed from theessential indicators of PPG content knowledge in 2018. The design stages, internalvalidation, trial I and trial II were carried out at the biology education campus of thePMIPA FKIP Riau University department. External validation was carried out atSMAN Plus Riau Province and SMAN 8 Pekanbaru. The quality of the guidebook isassessed from four aspects, namely, format and graphics, language, illustrations andimages as well as content aspects. The quality of the practicum video is also assessedfrom four aspects, namely material aspects, language, video quality, and presentationaspects. The guidebook and practical video produced in this study were validated byfive validators and respectively obtained a mean value of 3,52 and 3,59 with very validcategories. The test results of 20 seventh semester biology students respectivelyobtained an average score of 3,53 and 3,42 in the very good category. This shows thatmanuals and videos of practicum materials on food material testing for biology teachercandidates are appropriate to be used as independent learning resources to strengthenpracticum knowledge.Key Words: Handbooks, Practicum Videos, Food Ingredients Test